Antibody Response to Mycoplasma pneumoniae: Protection of Host and Influence on Outbreaks? - Dumke, Roger; Jacobs, Enno (Frontiers in Microbiology, 2016)
In humans of all ages, the cell wall-less and genome-reduced species Mycoplasma pneumoniae can cause infections of the upper and lower respiratory tract. The well-documented occurrence of major peaks in the incidence of community-acquired pneumonia cases reported world-wide, the multifaceted clinical manifestations of infection and the increasing number of resistant strains provide reasons for ongoing interest in the pathogenesis of mycoplasmal disease. The results of recent studies have provided insights into the interaction of the limited virulence factors of the bacterium with its host. In addition, the availability of complete M. pneumoniae genomes from patient isolates and the development of proteomic methods for investigation of mycoplasmas have not only allowed characterization of sequence divergences between strains but have also shown the importance of proteins and protein parts for induction of the immune reaction after infection. This review focuses on selected aspects of the humoral host immune response as a factor that might influence the clinical course of infections, subsequent protection in cases of re-infections and changes of epidemiological pattern of infections. The characterization of antibodies directed to defined antigens and approaches to promote their induction in the respiratory mucosa are also preconditions for the development of a vaccine to protect risk populations from severe disease due to M. pneumoniae.